Clinical Supervision and Management of U.S. Army Behavioral Health Technicians. (3rd July 2018) - Hoyt, Tim
ABSTRACT: For the past century, enlisted behavioral health technicians have played a significant paraprofessional role throughout the world in the provision of behavioral healthcare for the U.S. Army. This article reviews the background, training, and daily duty requirements of enlisted behavioral health technicians. Lessons learned for the training and supervision of enlisted behavioral health technicians are discussed, including active career engagement, using technicians with younger service members, and leveraging technicians who are licensed in other professional disciplines.